1988
DOI: 10.2343/geochemj.22.275
|View full text |Cite
|
Sign up to set email alerts
|

Magnesian calcite synthesis from calcium bicarbonate solution containing magnesium ions in the presence of fluoride and phosphate ions.

Abstract: Magnesian calcites were precipitated from 10 mM Ca(HCO3)2 (Ca 2+, 400 mg/1) solutions contain ing 35 or 53.5 mM Mg ions (Mg2+, 850 or 1300 mg/1) in the presence of fluoride and phosphate ions in various concentrations. Magnesian calcite formation from aqueous solution was favored by the presence of fluoride ions (0.5 to 2.5 mM) or phosphate ions (0.025 to 0.5 mM) in a parent solution. Aragonite and/or monohydrocalcite are formed below or above the critical concentrations of these ions. The presence of phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…This notion is supported by the fact that phosphate content in the foliated layer far exceeds that in the aragonitic shell layers [20]. One study identified phosphate as favorably controlling calcite formation when added to the calcium carbonate solution in trace amounts [39]. The precise effect of phosphate in polymorphism control awaits future study.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by the fact that phosphate content in the foliated layer far exceeds that in the aragonitic shell layers [20]. One study identified phosphate as favorably controlling calcite formation when added to the calcium carbonate solution in trace amounts [39]. The precise effect of phosphate in polymorphism control awaits future study.…”
Section: Discussionmentioning
confidence: 99%